2018
DOI: 10.1371/journal.pone.0203376
|View full text |Cite
|
Sign up to set email alerts
|

Novel sequence variants in the TLR6 gene associated with advanced breast cancer risk in the Saudi Arabian population

Abstract: Herein, we evaluated the association of the Toll-like receptor 6 (TLR6) single nucleotide polymorphisms (SNPs) rs3796508 (Val327Met) and rs5743810 (Ser249Pro) with breast cancer (BC) susceptibility in Saudi Arabian women, using in silico analysis. We found no significant differences in genotypic and allelic frequencies for rs3796508 between the BC patients (n = 127) and healthy individuals (n = 116). However, 86% of the BC patients, versus 98% of the healthy controls, carried the rs5743810 Pro allele (OR = 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…However, mortality could be decreased considerably via prevention strategies aimed at individuals who are identified as being at high risk (Weitzel, Blazer, Macdonald, Culver, & Offit, ). Semlali et al in 2018 identified novel single‐nucleotide polymorphisms (SNPs) in Toll‐like receptor 6 (TLR6) (rs5743810) that are associated with advanced BC risk in the Saudi Arabian population (Semlali et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, mortality could be decreased considerably via prevention strategies aimed at individuals who are identified as being at high risk (Weitzel, Blazer, Macdonald, Culver, & Offit, ). Semlali et al in 2018 identified novel single‐nucleotide polymorphisms (SNPs) in Toll‐like receptor 6 (TLR6) (rs5743810) that are associated with advanced BC risk in the Saudi Arabian population (Semlali et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the WHO, the global burden of cancer is expected to increase by the year 2040 to 27.5 million new cases and 16.3 million deaths as a result of population growth and aging [1]. In Saudi Arabia, cancer is very common due to the high rate of consanguinity and genetic factors [3,4] as it has been ranked as the second leading cause of deaths.…”
Section: Introductionmentioning
confidence: 99%
“…The major causes of IDA in Saudi Arabia include inadequate consumption of Vitamin C, infrequent consumption of red meat and fish, and genetic/or family history of IDA [ 8 , 10 ]. Several polymorphisms have been previously reported in the Saudi population as causative single nucleotide polymorphisms (SNPs) in diseases such as breast cancer [ 12 16 ], colon cancer [ 17 19 ], diffuse parenchymal lung disease [ 20 ], and acute myeloid leukemia [ 21 , 22 ]. In addition, genetic risk factors for IDA and causative genes have also been identified including the TMPRSS6 gene [ 23 ].…”
Section: Introductionmentioning
confidence: 99%